Mechanisms of designs inspired by nature and ways to develop them (Al-Academy, 2022)
Research in the field of biometric simulation is in the design of various and various industrial products, but it still needs new studies and research that are compatible with scientific and technological development, especially in the field of computing. Recognition, deduction, and simulation of nature, for example, the use of animal bones as tools in cutting, hunting or fighting, in addition to the use of animal drawings in cave drawings as symbols of strength, as well as dance movements and face painting to simulate the natural reality that surrounds humans. This trend developed to include simulation of nature in the formal and functional aspect to reach To vocabulary and solutions that help man in his daily life, the research problem is summarized in answering some questions, including what are the methods and methods that are used in bio-simulation and how to compare them, and is it possible to reach a new mechanism, but the objectives of the research were to reveal and compare the methodologies that address Biomimetics and the possibility of reaching a new mechanism in biomimetics. As for the research results, they were summarized as follows:1- There are a number of methodological approaches that describe the way in which biomimetics are solved.2- These methods only provide the way to achieve biomimetics, and their application is subject to the designer's direction and thinking.3- It is important to study the dynamic form in detail in order to get the basic idea of the design.